THE INFLUENCE OF THE BI RATE, ECONOMIC GROWTH, THIRD PARTY FUNDS (DPK), CAPITAL ADEQUACY RATIO (CAR), AND NON-PERFORMING LOANS (NPL) ON INDONESIAN BANK CREDIT DISTRIBUTION POST-COVID-19 PANDEMIC - Sabaruddin Siagian (Asosiasi Dosen Muda Indonesia, 2026)
The purpose of this study is to partially examine the influence of the BI Rate, economic growth, third-party funds (TPF), capital adequacy ratio (CAR), and non-performing loans (NPL) on Indonesian banking credit distribution after the Covid-19 pandemic. This research method uses a quantitative-statistical approach. The research data is sourced from commercial banks registered with the Financial Services Authority (OJK). The research data period is from the first quarter of 2022 to the first quarter of 2026. SPSS software is used to manage the research data. The results show that, post-Covid-19, the BI Rate, economic growth, CAR, and NPL have no significant effect on Indonesian banking credit distribution. Meanwhile, TPF has a positive and significant effect on Indonesian banking credit distribution.